DETECTION OF A RARE MUTATION IN A NOONAN SYNDROME SUSPECTED PATIENT: A CASE REPORT - Dobrevski, Boban; Shukarova Angelovska, Elena; Kirijas, Meri; Milanovski Gorjan; Brnjarchevska, Teodora; Boceska Frosina; Petlichkovski, Aleksandar (Croatian Society of Biologists in Health Care (CROBIH), 2020)
Noonan syndrome (NS) is a genetic autosomal dominant condition, caused by mutations in PTPN11 and other genes. The aim of this report is to highlight a finding of a rare mutation in the RAF1 gene in a six-year-old child evaluated for Noonan Syndrome. An Ampliseq Research Panel covering A2ML1, BRAF, CBL, HRAS, KRAS, MAP2K1, MAP2K2, NRAS, PTPN11, RAF1, RIT1, SHOC2, SOS1 and SPRED1 genes was used on the Ion Torrent platform. Out of 54 variants detected, a single nucleotide missense mutation c.483T>G in the RAF1 gene was classified as likely pathogenic, based on a single previous submission to Clinvar. Further investigations may shed light on the possible role of this variant in the pathogenesis of Noonan Syndrome and other RASopathies.
Keywords: Noonan syndrome; RASopathies